Volume 1: Aircraft Engine; Ceramics; Coal, Biomass and Alternative Fuels; Education; Electric Power; Manufacturing Materials An 2010
DOI: 10.1115/gt2010-22628
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Duty Gas Turbine Simulation: A Compressor IGV Airfoil Off-Design Characterization

Abstract: The correct simulation of power plant behavior over a variety of operating conditions has to be extremely detailed in order to provide reliable help to the turbomachinery developers. The latter instance implies for designers and commercial personnel to be equipped with reliable calculation tools (in-house developed or commercial). In particular, Performance Analysis Codes (PACs) allow the designers to analyze different system configurations. To predict off-design behavior, these codes need to be not limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…25 Moreover, there are some factors such as generating the proper compressor and turbine maps, the effect of Bleed valve and inlet guide vane (IGV) valve on the compressor map that make the physical modelling problem become more complex. 26,27 One solution is to provide a simplified mathematical model that consists of a set of algebraic equations and simple time delay controllers. 28 However, the applications of gas turbine systems depend greatly on the accuracy of the system model and governor parameters.…”
Section: Gas Turbine Modelling Preliminariesmentioning
confidence: 99%
“…25 Moreover, there are some factors such as generating the proper compressor and turbine maps, the effect of Bleed valve and inlet guide vane (IGV) valve on the compressor map that make the physical modelling problem become more complex. 26,27 One solution is to provide a simplified mathematical model that consists of a set of algebraic equations and simple time delay controllers. 28 However, the applications of gas turbine systems depend greatly on the accuracy of the system model and governor parameters.…”
Section: Gas Turbine Modelling Preliminariesmentioning
confidence: 99%
“…Variable inlet guide vanes (VIGVs) are widely used in axial-flow compressor and other fluid-machines [1][2][3] to provide the requested flow angle into downstream rotor to improve the compressor efficiency and stall margin at off-design conditions. 4,5 Research indicated that as the stagger angle increases the VIGV gradually comes into the high incidence operation conditions and the leading edge velocity spike induced flow separation arises leading to the rapid increase of losslevel, 6,7 which can cause considerable reduction of compressor efficiency. Therefore, some researchers proposed a new VIGV airfoil featuring "dual-peak" surface velocity distribution which can suppress the flow separation and achieve much lower loss-level at high incidence in two-and three-dimensional cases.…”
Section: Introductionmentioning
confidence: 99%